2016
DOI: 10.1016/j.jpsychores.2016.09.005
|View full text |Cite
|
Sign up to set email alerts
|

What's ‘difficult’? A multi-stage qualitative analysis of secondary care specialists' experiences with medically unexplained symptoms

Abstract: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-pro t purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 51 publications
(48 reference statements)
0
11
0
Order By: Relevance
“…Doctors in many countries are discussing how to deal with patients who have somatization symptoms [24]. In particular, doctors who do not specialize in psychological treatment have a tendency to think that patients suffering from a somatization symptom are “difficult” to deal with [25] and seem to think that it takes more energy to take care of such patients than regular patients. In fact, in this study eight patients who had a diagnosis of an organic disease complained about malaise and, accordingly, it took more effort to determine these patients’ major complaints than those of usual patients.…”
Section: Discussionmentioning
confidence: 99%
“…Doctors in many countries are discussing how to deal with patients who have somatization symptoms [24]. In particular, doctors who do not specialize in psychological treatment have a tendency to think that patients suffering from a somatization symptom are “difficult” to deal with [25] and seem to think that it takes more energy to take care of such patients than regular patients. In fact, in this study eight patients who had a diagnosis of an organic disease complained about malaise and, accordingly, it took more effort to determine these patients’ major complaints than those of usual patients.…”
Section: Discussionmentioning
confidence: 99%
“…Yon et al found that junior doctors feel incompetent in working with patients with medically unexplained symptoms and frustrated and anxious by this [ 32 ]. Without a more helpful model, they categorise patients as malingers or mentally ill. Maatz et al discussed the concept of ‘difficult’ to treat MUS patients and the negative reactions that can occur when secondary care physicians face these patients and feel frustrated and unable to help them [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sign Similar to other complex or atypical presentations, many patients are not diagnosed accurately in the early stages and even if they are, feelings of frustration and uncertainty often develop in both patient and doctor. 4 Doctors may feel powerless and inadequate and often refer such patients for further investigations or opinions. 5 As illustrated in this example, patients can become stuck in a fruitless succession of medical appointments without resolution of problems.…”
Section: Categorymentioning
confidence: 99%